Penerapan Taksonomi Bloom dalam Pembelajaran Tematik SD IT Amani Ar Rasyid Cengkareng - Ina Magdalena; Lusiana Della Paramita; Zahra Khoerunisa; Melinda Nur Utami; Eneng Emiliani Amardani (Jurnal Halaqah, 2020)
The purpose of this journal is to explain the application of Bloom’s Taxonomy in thematic learning at SD IT Amani Ar Rasyid Cengkareng. This research uses a qualitative descriptive approach through interviews. The use of Bloom Taxonomy theory in the assessment or evaluation system is considered very effective because the application of the Bloom Taxonomy must be analyzed in advance to the level of needs and characteristics of students or learners who are the subject of these studies in SD IT Amani Ar Rasyid Cengkareng.